Q. 23.9( 9 Votes )

# If f(x) = (x – a)

Answer :

Given f(x) = (x – a)2(x – b)2

We need to find f(a + b).

We have f(a + b) = (a + b – a)2(a + b – b)2

f(a + b) = (b)2(a)2

f(a + b) = a2b2

Thus, f(a + b) = a2b2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Let A = {–1, 0, 1RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Let <span lang="EMathematics - Exemplar

Let <span lang="EMathematics - Exemplar

Express the functRD Sharma - Mathematics

Let <span lang="EMathematics - Exemplar

. Let f:(2,RS Aggarwal - Mathematics

. Let f: R RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Find the values oMathematics - Exemplar